Questioning the methodologic superiority of 'placebo' over 'active' controlled trials. - Howick, J (2009)
A resilient issue in research ethics is whether and when a placebo-controlled trial (PCT) is justified if it deprives research subjects of a recognized treatment. The clinicians' moral duty to provide the best available care seems to require the use of 'active' controlled trials (ACTs) that use an established treatment as a control whenever such a therapy is available. In another regard, ACTs are supposedly methodologically inferior to PCTs. Hence, the moral duty of the clinical researcher to use the best methods will favor PCTs. In this target article, I analyze the three reasons for believing that ACTs are inferior to PCTs namely: 1) ACTs lack 'assay sensitivity'; 2) ACTs do not measure absolute effect size; and 3) ACTs require more participants; and I contend that none are acceptable. Consequently the tension between clinical and research ethics dissolves: the moral duty of the clinician to avoid PCTs is unopposed by methodological considerations.